OMERACT Endorsement of Patient-reported Outcome Instruments in Antineutrophil Cytoplasmic Antibody-associated Vasculitis - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2017)
Objective. The antineutrophil cytoplasmic antibody-associated vasculitides (AAV) are multiorgan diseases. Patients with AAV report impairment in their health-related quality of life (HRQOL) and have different priorities regarding disease assessment compared with physicians. The Outcome Measures in Rheumatology (OMERACT) Vasculitis Working Group previously received endorsement for a core set of domains in AAV. Two approaches to measure patient-reported outcomes (PRO) were presented at OMERACT 2016. Methods. A novel 5-step tool was used to facilitate assessment of the instruments by delegates: the OMERACT Filter 2.0 Instrument Selection Algorithm, with a red-amber-green checklist of questions, including (1) good match with domain (face and content validity), (2) feasibility, (3) do numeric scores make sense (construct validity)?, (4) overall ratings of discrimination, and (5) can individual thresholds of meaning be defined? Delegates gave an overall endorsement. Three generic Patient-Reported Outcomes Measurement Information System (PROMIS) instruments (fatigue, physical functioning, and pain interference) and a disease-specific PRO, the AAV-PRO (6 domains related to symptoms and HRQOL), were presented. Results. OMERACT delegates endorsed the use of the PROMIS instruments for fatigue, physical functioning, and pain interference (87.6% overall endorsement) and the disease-specific AAV-PRO instrument (89.4% overall endorsement). Conclusion. The OMERACT Vasculitis Working Group gained endorsement by OMERACT for use of the PROMIS and the AAV-PRO in clinical trials of vasculitis. These instruments are complementary to each other. The PROMIS and the AAV-PRO need further work to assess their utility in longitudinal settings, including their ability to discriminate between treatments of varying efficacy in the setting of a randomized controlled trial.
Keywords: ANCA-ASSOCIATED VASCULITIS; PATIENT-REPORTED OUTCOMES; PROMIS; ICF; OMERACT; QUALITY-OF-LIFE; ANCA-ASSOCIATED VASCULITIS; WEGENERS-GRANULOMATOSIS; CLINICAL-TRIALS; CORE SET; INVOLVEMENT